Sosialisasi dan Focus Group Discussion Pencegahan Serta Penanganan Stunting Sejak Dini di Desa Sumberanyar Kabupaten Bondowoso - Rizki Rismawati; Siska Aula Alfianti; Iraudatul Hasanah; Syahroni Riskiyono; Danu Indra Wardhana; Trias Setyowati (Journal of Community Development, 2023)
Stunting is a condition where children under 5 years of age cannot grow due to chronic malnutrition, causing them to be shorter than their age. The aim of this socialization is to identify the stunting problem in Sumberanyar village as well as present material on preventing and handling stunting in Sumberanyar village. The implementation method gathered midwives, 10 posyandu cadres, posyandu members in the PKK room at the Sumberanyar village hall. Next was the presentation of material about preventing and handling stunting, then conducting a Focus Group Discussion (FGD). In this activity, the results of the formulation of the stunting problem in Sumberanyar Village were obtained, namely, cigarette smoke, mother's knowledge, snack food, and the habit of defecating in the river. Meanwhile, activities that have been carried out by midwives and Posyandu cadres to prevent stunting include giving worm medicine, giving supplementary food (PMT), latrine building programs, classes for pregnant women and measuring children's height and weight. Based on the activities that have been carried out, it is known that 60% of posyandu cadres and posyandu members have a good level of knowledge and 40% have sufficient abilities before participating in socialization activities. Furthermore, after carrying out socialization regarding the prevention and handling of stunting, the number of posyandu cadres and posyandu members who had a good level of knowledge increased to 80% and the level of sufficient knowledge became 20%. This activity can also help posyandu cadres and members get better information that focuses on preventing and handling stunting.